Modulation of excitonic response in colloidal low-dimensional nanomaterials - Yu, Junhong (Nanyang Technological University, 2020)
Colloidal low-dimensional nanomaterials (CLDNMs), benefitting from the solution-processability, quantum-confinement effect and high quantum efficiency, are prominent candidates to prevent the end of Moore’s law and maintain the ever-accelerating progress in the field of optoelectronics. In the last two decades, tremendous research efforts have been concentrated on monitoring, understanding the photophysics in CLDNMs and uncovering that confined excitons are responsible for these extraordinary properties. Therefore, the daunting challenge to realize the potential of these CLDNMs in practical applications is to control, manipulate and eventually modulate the excitons. Considering the limitation of extensively investigated quantum confinement engineering based- or chemical structure engineering based-modulation, how to master intra- and inter-particle excitonic processes in CLDNMs via newly-developed technologies are crucial for future innovation. This thesis is devoted to the study of excitonic modulation of CLDNMs beyond the conventional quantum confinement engineering based- or chemical composition based-methods, through both synthesis modification and post-synthesis treatment. Specifically, for excitonic modulation during synthesis process, we proposed that doped transition metal ions (e.g., Cu, Ag or Mn) can be utilized to generate an anisotropic Coulomb environment in the CLDNM host and thus, modulate the intrinsic properties of excitonic carriers. For excitonic modulation under post-synthesis condition, we first explored the usage of Förster resonance energy transfer (FRET) as a tool-kit to modulate the inter-particle excitonic processes in the assembly of two distinct CLDNMs. We then studied the interaction between excitons in CLDNMs and localized surface plasmon (LSP) sustained in metallic nanostructures to convert the energy stored in excitons into the bosonic quasi-particles (polaritons). Finally, we investigated the effect of excess electrons in the conduction band on the excitonic gain performance of CLDNMs. For synthesis modification, our key achievements include demonstration of room-temperature biexciton emission under continuous-wave excitation enabled by dopant-host interaction and ultra-low threshold biexciton lasing resulted from reduced Coulomb screening; For post-synthesis treatment, our main contributions are reflected in: i). Designing an all-optical strategy to manipulate the exciton flow between the donor-acceptor pair through stimulated emission mediated FRET and breaking the limitation of unidirectional exciton flow in conventional binary FRET scheme by utilizing the d orbital electrons in dopants; ii). For the first time, demonstrating that the ultrastrong exciton-plasmon coupling (Rabi energy larger than 400 meV) and high cooperativity (exceeding 11) can be achieved using Wannier-Mott excitons; iii). In a long-sought practical device, revealing that the negative Trion can be utilized to tune the excitonic gain performance. Our works have proposed and demonstrated several new ways to modulate the excitonic processes in CLDNMs. The developed concepts, mechanisms and methods can be readily applied to other quantum-confined systems (e.g., perovskites and 2D transition metal dichalcogenides). We hope that these works can play the role of throwing out a minnow to catch a whale, in the development of excitonic or optoelectronic devices.